Association of age-related hearing loss with cognitive impairment and dementia: an umbrella review - Ying, Guo; Zhao, Guangran; Xu, Xianpeng; Su, Su; Xie, Xin (Frontiers in Aging Neuroscience, 2023)
Background: Hearing loss, cognitive impairment and dementia have become common problems for older adults. Currently, systematic reviews and meta-analyses of the association between age-related hearing loss (ARHL) with cognitive impairment and dementia may have inconsistent results. To explore and validate the association between ARHL with cognitive impairment and dementia through summarizing and evaluating existing evidence.Method: From inception to February 01, 2023, PubMed, Web of Science, Embase, and Cochrane Library databases were systematically searched. AMSTAR 2 was used to evaluate methodological quality and GRADE system was used to evaluate evidence quality. We summarized the basic characteristics of the included studies and extracted effect data for ARHL with cognitive impairment and dementia. Forest plots were used to describe the relative risk associated with ARHL and cognitive impairment, and the relative risk associated with ARHL and dementia, respectively.Results: A total of 11 systematic reviews and meta-analyses met the inclusion criteria. Overall, the methodological quality of the included SRs/MAs was moderate and the quality of the evidence was low. The combined results found that the pooled risk ratio of ARHL and cognitive impairment was 1.30(random-effects; 95% CI 1.16 to 1.45), and the pooled risk ratio of ARHL and dementia was 1.59 (random-effects; 95% CI 1.34 to 1.90).Based on the evidence reported in this umbrella review, age-related hearing loss is significantly associated with cognitive impairment and dementia. Hearing loss may be a high risk factor for cognitive impairment and dementia in older adults.Age-related hearing loss (ARHL) is a prevalent complex sensory deficit among older adults, resulting from the cumulative effects of aging on the auditory system [1]. The deprivation of hearing in older adults due to ARHL could distance them from regular social activities, potentially leading to social isolation, loneliness, cognitive impairment, and an elevated risk of frailty and falls [2,3]. The count